Pengobatan babesiosis dan ehrlichiosis yang terjadi bersamaan pada anjing menggunakan imidocarb dipropionate dan doksisiklin. - I Gde Andhika Putra Pratama; Putu Ayu Sisyawati Putriningsih; I Gusti Made Krisna Erawan (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2025)
Rhipicephalus sanguineus is a well-recognized vector of tick-borne diseases, including babesiosis and ehrlichiosis, in dogs. This case report describes the successful therapeutic management of concurrent babesiosis and ehrlichiosis using imidocarb dipropionate and doxycycline. A 10-month-old male domestic dog presented with anorexia, weakness, pyrexia, erythema on the medial aspect of the hind limb, and heavy tick infestation. Complete blood count analysis revealed leukopenia, granulocytopenia, increased mean corpuscular volume and mean corpuscular hemoglobin, and thrombocytopenia. Blood smear examination revealed the presence of intraerythrocytic parasites and Ehrlichia morulae within the monocytes. In addition, a rapid antibody test yielded positive results for Babesia spp. and Ehrlichia spp. The dog was treated with a comprehensive therapeutic regimen consisting of fluralaner, imidocarb dipropionate, doxycycline, and supportive supplementation with multi-vitamins and minerals. Twenty-eight days after initiation of therapy, the dog showed marked clinical improvement, as evidenced by the absence of blood-borne pathogens on smear examination and substantial recovery of hematological parameters